2022
DOI: 10.1001/jamanetworkopen.2022.22070
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Progression of Metabolic Risk Factors in Diabetes Development

Abstract: This cohort study uses data from the Atherosclerosis Risk in Communities (ARIC) Study to investigate whether the increase in metabolic syndrome severity is more pronounced in women than men and whether the sex difference varies by race.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…Importantly, sex differences have been observed for the aetiology and progression of cardiometabolic risk factors ( Gerdts and Regitz-Zagrosek, 2019 , Yoshida et al, 2022 ) and their relation to the brain ( Alqarni et al, 2021 , Subramaniapillai et al, 2021 , Subramaniapillai et al, 2022 , Than et al, 2022 ), illustrating the critical need for sex-specific studies ( Miller and Spencer, 2014 , Shansky and Murphy, 2021 , Taylor et al, 2019 ). Further research is necessary to understand the complex interplay of mechanisms that contribute to risk for cardiometabolic and neurodegenerative diseases in post-menopausal females ( Christensen and Pike, 2015 ), and how preventive measures such as physical exercise and hormone replacement therapy can be optimised to moderate risk.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, sex differences have been observed for the aetiology and progression of cardiometabolic risk factors ( Gerdts and Regitz-Zagrosek, 2019 , Yoshida et al, 2022 ) and their relation to the brain ( Alqarni et al, 2021 , Subramaniapillai et al, 2021 , Subramaniapillai et al, 2022 , Than et al, 2022 ), illustrating the critical need for sex-specific studies ( Miller and Spencer, 2014 , Shansky and Murphy, 2021 , Taylor et al, 2019 ). Further research is necessary to understand the complex interplay of mechanisms that contribute to risk for cardiometabolic and neurodegenerative diseases in post-menopausal females ( Christensen and Pike, 2015 ), and how preventive measures such as physical exercise and hormone replacement therapy can be optimised to moderate risk.…”
Section: Discussionmentioning
confidence: 99%
“…50 Analysis of data from the ARIC Study (Atherosclerosis Risk in Communities) revealed that women experienced a greater increase in metabolic syndrome severity, central adiposity, and triglycerides than men in the prediabetes state, which may explain women’s disadvantage in diabetic cardiovascular disease risk. 51…”
Section: Discussionmentioning
confidence: 99%
“…50 Analysis of data from the ARIC Study (Atherosclerosis Risk in Communities) revealed that women experienced a greater increase in metabolic syndrome severity, central adiposity, and triglycerides than men in the prediabetes state, which may explain women's disadvantage in diabetic cardiovascular disease risk. 51 No-reflow after recanalization therapy has been reported in many clinical trials. [16][17][18] Our present data, on the other hand, show that the capillary reperfusion in penumbra in control mice did not differ from baseline at 24 hours post-MCAO.…”
Section: Go Red For Womenmentioning
confidence: 99%
“…The factors contributing to sex-related differences in relative risk of CV events is still a subject of debate. It has been suggested that deterioration in glucose homeostasis from normal glucose tolerance to prediabetes to overt T2DM is associated with worsening in metabolic risk pro le and target organ damage in women than men (5,(11)(12)(13)(14)(15). CV risk factors progress during menopausal transition, determining greater accumulation of fat in visceral and ectopic tissues and aggravating insulin resistance, in ammation and dyslipidemia in women with T2DM (16).…”
Section: Introductionmentioning
confidence: 99%
“…CV risk factors progress during menopausal transition, determining greater accumulation of fat in visceral and ectopic tissues and aggravating insulin resistance, in ammation and dyslipidemia in women with T2DM (16). Moreover, it has been hypothesized that hyperglycaemia has a stronger effect on CV risk factors in women than men (5,(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%